2013
DOI: 10.1017/s1743921314000684
|View full text |Cite
|
Sign up to set email alerts
|

The nuclear cluster of the Milky Way: total mass and luminosity

Abstract: Here we present the fundamental properties of the nuclear cluster of the Milky Way. First, we derive its structural properties by constructing a density map of the central 1000 using extinction-corrected star counts. We can describe the data with a two-component model built from Sersic profiles. The inner nearly spherical component is the nuclear cluster. The outer, strongly flattened component can be identified with the stellar component of the circumnuclear zone. Second, we enlarge the radius inside which de… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
12
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(19 citation statements)
references
References 140 publications
(569 reference statements)
4
12
3
Order By: Relevance
“…Becklin & Neugebauer 1968, Launhardt et al 2002, Graham & Spitler 2009, Schödel 2011, Fritz et al 2014 as well as with the results of kinematic modeling of the MWNSC (see section 5). But, in contrast to the previous work, Schödel et al (2014) showed, for the first time, that the MWNSC is not spherically symmetric and derived the intrinsic shape and overall properties of the MWNSC without having to rely on assumptions about the symmetry or centering of the cluster in projection on the plane of the sky.…”
Section: Overall Properties Of the Mwnscmentioning
confidence: 87%
See 4 more Smart Citations
“…Becklin & Neugebauer 1968, Launhardt et al 2002, Graham & Spitler 2009, Schödel 2011, Fritz et al 2014 as well as with the results of kinematic modeling of the MWNSC (see section 5). But, in contrast to the previous work, Schödel et al (2014) showed, for the first time, that the MWNSC is not spherically symmetric and derived the intrinsic shape and overall properties of the MWNSC without having to rely on assumptions about the symmetry or centering of the cluster in projection on the plane of the sky.…”
Section: Overall Properties Of the Mwnscmentioning
confidence: 87%
“…Assuming spherical symmetry, recent studies (e.g. Trippe et al 2008, Do et al 2013b, Fritz et al 2014 found that the central cluster kinematics is consistent with being isotropic (i.e. β=0).…”
Section: Kinematics Of the Mwnscmentioning
confidence: 94%
See 3 more Smart Citations